KEWAJIBAN REHABILITASI MEDIS KORBAN PENYALAHGUNAN NARKOTIKA - Zainab Ompu Jainah (KEADILAN PROGRESIF, 2020)
Rehabilitation is one of the government's efforts to tackle narcotics abuse. This effort is an alternative effort or action, because the perpetrators of narcotics abuse are also victims of narcotics addiction that requires treatment or care. This treatment or treatment is carried out through rehabilitation facilities. The research problem that will be discussed in this research is how the procedure of implementing medical rehabilitation for narcotics abuse victims, the method of using Normative Juridical Approach and Empirical Approach, the source of data is obtained from the field and library. Types of data obtained secondary data and primary data Data collection is done by means of library studies and subsequent studies were analyzed quantitatively. Based on the results of research and discussion, it is known that the procedure for implementing medical rehabilitation for narcotics abuse victims based on PERBER / 01/111/2014 / BNN, namely narcotics addicts who have received a court decision to undergo treatment or treatment through rehabilitation, is submitted by the prosecutor's office to a medical rehabilitation facility the appointed narcotics convict is accompanied by the minutes of the court decision and signed by the patient and family / guardian. Suggestions that can be delivered It is hoped that for law enforcement, in this case the judge is brave to decide a heavy sentence in accordance with the law. And the Provincial Narcotics Agency is making more serious efforts in preventing narcotics abuse by involving all law enforcement authorities.